ИНГЛИС ТИЛИНДЕГИ ФЕЙИЛ СӨЗЛЕРДИҢ КОНВЕРСИЯ, КОМПОЗИЦИЯ УСЫЛЫ МЕНЕН БЕРИЛИЎ ЖОЛЛАРЫ - Утепбергенова, Д.; Джумамуратова, Г. (SCIENCE and SOCIETY, 2021)
Formation of verbs in English with the help of lexical morphological style, ways of transmission of verbs by conversion, composition style. Conditions of formation and specific rendering of verbs in English, formation of verbs by synthetic and analytical methods and its place in the system of word formation. Making verbs with affixation style in English. Use of words with conversion style in English. In English, we create verbs from each word group through conversion.
Keywords: conversion; composition; noun; verb; affix; suffix; word formation; form formation; semantic structure; synthetic and analytical methods